1972
DOI: 10.1007/bf01896334
|View full text |Cite
|
Sign up to set email alerts
|

Cavities in the reefs of the Wenlock Limestone (Mid-Silurian) of Shropshire, England

Abstract: ZusammenfassungStudien der Wuchsformen und des inneren Baues yon Organismen der Wenloek-Rifle zeigen, dab Hohlr~iume w~ihrend des Riffwachstums zwischen einzelnen RiffstSeken, zwisehen individuellen Kolonien sowie zwischen dem Geriist und im Inneren der Skelette yon Riffbildnern vorhanden waren. Nur vollkommen abgesehlossene, konstruktive Hohlr~iume sind w~hrend der Sedimentation in den Riffen nicht mit Ablagernngen gefiillt worden. Die Lage und Natur diagenetischer Hohlr~iume werden yon den Wuchsformen der Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The downward-pointing growth direction of pendant bushy mesoclots in the thrombolite reef (Fig. 4 B, C) indicates that at one time sea water flowed beneath the mesoclots (Scoffin 1972;James and Gravestock 1990). It is concluded that hypothesis 1 (13A, B) accounts best for the formation of the large reef cavities (Fig.…”
Section: Formation Of Large Reef Cavitiesmentioning
confidence: 89%
See 1 more Smart Citation
“…The downward-pointing growth direction of pendant bushy mesoclots in the thrombolite reef (Fig. 4 B, C) indicates that at one time sea water flowed beneath the mesoclots (Scoffin 1972;James and Gravestock 1990). It is concluded that hypothesis 1 (13A, B) accounts best for the formation of the large reef cavities (Fig.…”
Section: Formation Of Large Reef Cavitiesmentioning
confidence: 89%
“…In both hypotheses, creation of large cavities involves the abilities of Angulocellularia and renalcid microorganisms to calcify rapidly (Kobluk and James 1979;Turner et al 2000), and to grow in all possible directions including upwards and laterally (Kobluk and James 1979;Pratt and James 1982;Pratt 1984;Riding 1991aRiding , 1991b) (Figs. 4B, C, 5 D, F), making it possible for the mesoclots to create elevated prominences (Scoffin 1972;James 1983) with lateral extensions that could merge to roof-over spaces that were centimeters to meters deep and/or wide to create growth framework cavities (Figs. 3, 13).…”
Section: Formation Of Large Reef Cavitiesmentioning
confidence: 99%
“…Similarly, the ceilings and overhangs near the MLW level are interpreted to result from lateral growth which became dominant when vertical growth was curbed by sea-level. SCOFFIN (1972) ascribed the formation of overhangs and cavities in Recent Bermuda reefs and Silurian reefs of Shropshire (England) to. frame growth, thus providing additional examples for the growth pattern suggested e).…”
Section: Discussionmentioning
confidence: 98%
“…Coelobiontic bryozoans are not common; they occur in less than 20% of the cavities, and appear to be less important than in some other described lower and middle Paleozoic reef cavities (e.g., Scoffin 1972;Spjeldnaes 1974;Kobluk 1980).…”
Section: Bryozoansmentioning
confidence: 97%
“…Among them are reports of Cambrian coelobionts by Kobluk and James (1979), Kobluk (1979), Brasier (1976, Ordovician coelobionts by Brett and Liddell (1978), Kobluk and Karolyi (1978), and Kobluk (1980), and Silurian coelobionts by Scoffin (1972) and Spjeldnaes (1974). Later Paleozoic coelobionts are reported by Newell et al (1953), Bonem (1977), and Flugel (1977).…”
Section: Introductionmentioning
confidence: 96%